Tổng hợp perovskit La0,9Ce0,1Cr0,5Mn0,5O3 ở nhiệt độ thấp bằng phương pháp đốt cháy gel - Đại, Lưu Minh; Dũng, Nguyễn Xuân (Vietnam Journal of Chemistry, 2012)
La0.9Ce0.1Cr0.5Mn0.5O3 has been synthesized at temperature 650oC by the combustion of gel prepared from polyvinyl alcohol (PVA) and metal nitrates. La0.9Ce0.1Cr0.5Mn0.5O3 characterization is examined by X-ray diffraction (XRD), thermogravimetric and differential thermal analysis          (TG-DTA), transmission  electron  microscopy (TEM) and BET (Brunaure-Emmet-Teller) measurements. The obtained  sample under optional preparative conditions  has nano scale with specific square area of 16.0 m2/g.